Silicon on Isolator Ribbon Field-Effect Nanotransistors for High-Sensitivity Low-Power Biosensors - Nikolay Masalsky (Journal of Engineering and Technological Sciences, 2022)
Silicon field-effect transistors (FETs) are an established technology for sensing applications. Recent advancements and the use of high-performance multigate FETs in computing technology raise new opportunities and questions about the most suitable device sensing architecture. In this work, we propose pH sensors exploiting ribbon (tri-date) FETs fabricated on investigated silicon nanowires and silicon-on-insulator substrates by a fully CMOS compatible approach. The FET characteristics were optimized using 3D modeling performed by the TCAD computer-aided design software package, depending on the topological parameters of the transistor and the level of control voltage. N-channel fully depleted ribbon FETs with critical dimensions in the order of 30 nm and SiO2 as a subgate insulator were developed and characterized. It was established that thin structures with a width of slightly than more 100 nm, a thickness of 40 nm, and a reduced doping level have high sensitivity and low energy consumption. They showed excellent electrical properties, subthreshold swing (SS) was about 90 mV/dec, and the on-to-off current ratio, Ion/Ioff, was about 105. The same architecture was tested as a highly sensitive, stable and reproducible pH sensor. The average internal sensitivity, S, was equal 34 mV/pH or 360 nA/pH. Sensitivity to pH, estimated in terms of relative changes in the threshold voltage, was 74%, and the maximum drain current was 40%. The maximum drain current of 85 μA at V ds = 1.0 V suggests successful low-power operation of the proposed device.